Public Trust in Government and Future Anxiety Among Generation Z: A Systematic Literature Review and an Integrated Conceptual Framework - Fharil Yosafat Panungkelan; Suhadianto Suhadianto; IGAA Noviekayati (CV. ITTC INDONESIA, 2026)
governance challenges, including rapid digital transformation, political polarization, and macroeconomic uncertainty. Despite its growing importance, a significant theoretical gap persists regarding how institutional trust interacts with the psychological well-being of young adults, specifically concerning the future anxiety experienced by Generation Z. This systematic literature review integrates fragmented, interdisciplinary evidence from public administration, political science, developmental psychology, and digital governance to address this disconnect. Adhering strictly to the PRISMA 2020 guidelines and the SPAR-4-SLR framework, this study synthesizes empirical and theoretical evidence published between January 2021 and June 2026 to explore how digital governance structures and institutional trust shape the future orientation of young citizens. The thematic synthesis reveals a distinct